Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/sj.onc.1205879
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced death in neuroblastoma does not involve death receptors in S-type cells and is caspase-independent in N-type cells

Abstract: Death induced by doxorubicin (dox) in neuroblastoma (NB) cells was originally thought to occur via the Fas pathway, however since studies suggest that caspase-8 expression is silenced in most high stage NB tumors, it is more probable that dox-induced death occurs via a different mechanism. Caspase-8 silenced N-type invasive NB cell lines LAN-1 and IMR-32 were investigated for their sensitivity to dox, and compared to S-type noninvasive SH-EP NB cells expressing caspase-8. All cell lines had similar sensitiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
(25 reference statements)
3
36
1
Order By: Relevance
“…The wild-type p53-expressing SH-SY5Y line was purchased from ATCC (Manassas, VA, USA). The wild-type p53 status was demonstrated in previous reports (IMR32: Hopkins-Donaldson et al, 2002;SK-N-SH: Wolff et al, 2001) and p53 sequencing, which was performed according to the previous report (Tweddle et al, 2001), confirmed the wild-type p53 status in these cell lines. In terms of the copy number of MYCN by Southern blot analysis, SH-SY5Y, SK-N-SH and NB-69 are single-copy NB cells; NB-9, IMR32, NB-1 and NB-19 cells have 50, >150, >150 and 25 copies, respectively (data not shown).…”
Section: Cells and Cell Culturesupporting
confidence: 76%
“…The wild-type p53-expressing SH-SY5Y line was purchased from ATCC (Manassas, VA, USA). The wild-type p53 status was demonstrated in previous reports (IMR32: Hopkins-Donaldson et al, 2002;SK-N-SH: Wolff et al, 2001) and p53 sequencing, which was performed according to the previous report (Tweddle et al, 2001), confirmed the wild-type p53 status in these cell lines. In terms of the copy number of MYCN by Southern blot analysis, SH-SY5Y, SK-N-SH and NB-69 are single-copy NB cells; NB-9, IMR32, NB-1 and NB-19 cells have 50, >150, >150 and 25 copies, respectively (data not shown).…”
Section: Cells and Cell Culturesupporting
confidence: 76%
“…Blocking Caspase activation did not prevent cell killing in leukemic blast cells and neuroblastoma cells induced by chemotherapeutics including doxorubicin [16;17]. Additionally, doxorubicin induced death in neuroblastoma cells is also Caspase-independent [18] and Caspase inhibition switches doxorubicin induced apoptosis to senescence [17]. These data strongly suggest that additional factors play a pivotal role in cell death.…”
Section: Introductionmentioning
confidence: 80%
“…Activation of caspases seems not to be mandatory for cell death upon doxorubicin [16][17][18] suggesting the presence of additional factors. In the last decade numerous reports highlight the potential role of cathepsin B in controlling apoptosis but its role in drug induced apoptosis has not been addressed in a systematic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are particularly relevant because DFMO and SAM486A cause rapid and prolonged growth inhibition of two MYCN-amplified NB cell lines, which (1) are representative of MYCN-amplified tumors with aggressive behavior, and (2) are deficient in p53. Mutated p53 is often associated with relapsed and more progressive tumors, which circumvent p53-mediated apoptosis and exhibit chemoresistance (Hopkins-Donaldson et al, 2002). Since DFMO and SAM486A have been recently evaluated in Phase III and Phase II human trials, respectively (Levin et al, 2003;Pless et al, 2004), there is considerable information available regarding their concurrent side effects, pharmacokinetics, and maximum tolerated doses.…”
Section: Discussionmentioning
confidence: 99%